2007
DOI: 10.1007/s00213-007-0957-y
|View full text |Cite
|
Sign up to set email alerts
|

Single dose of a dopamine agonist impairs reinforcement learning in humans: Behavioral evidence from a laboratory-based measure of reward responsiveness

Abstract: Rationale-The dopaminergic system, particularly D2-like dopamine receptors, has been strongly implicated in reward processing. Animal studies have emphasized the role of phasic dopamine (DA) signaling in reward-related learning, but these processes remain largely unexplored in humans.Objectives-To evaluate the effect of a single, low dose of a D2/D3 agonist-pramipexole-on reinforcement learning in healthy adults. Based on prior evidence indicating that low doses of DA agonists decrease phasic DA release throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
196
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 199 publications
(226 citation statements)
references
References 67 publications
26
196
1
Order By: Relevance
“…There are good reasons to suppose that the subjective (Hamidovic et al, 2008) and behavioral (Pizzagalli et al, 2008;Riba et al, 2008;Santesso et al, 2009) effects of low doses of dopaminergic agents reflect pre-synaptic actions at the auto-receptors that regulate the activity of mid-brain dopaminergic neurons (Frank and O'Reilly, 2006;Grace, 1995). As described below, we replicate findings that single (1 mg) low doses of PPX reduce psychometric measurements of state-positive affect in healthy adults and that have been taken to suggest a presynaptic mode of action (Hamidovic et al, 2008).…”
Section: Participants and Designssupporting
confidence: 70%
See 2 more Smart Citations
“…There are good reasons to suppose that the subjective (Hamidovic et al, 2008) and behavioral (Pizzagalli et al, 2008;Riba et al, 2008;Santesso et al, 2009) effects of low doses of dopaminergic agents reflect pre-synaptic actions at the auto-receptors that regulate the activity of mid-brain dopaminergic neurons (Frank and O'Reilly, 2006;Grace, 1995). As described below, we replicate findings that single (1 mg) low doses of PPX reduce psychometric measurements of state-positive affect in healthy adults and that have been taken to suggest a presynaptic mode of action (Hamidovic et al, 2008).…”
Section: Participants and Designssupporting
confidence: 70%
“…Changes in reinforcement learning following treatment with PPX (Pizzagalli et al, 2008) are associated with altered signalling within the anterior cingulate region following bad outcomes (Santesso et al, 2009) and blunted signalling within the striatum following good outcomes (Riba et al, 2008). Previously, we have observed that attenuated neural responses to bad gambling outcomes within the anterior cingulate sulcus is also associated with continued chasing behavior during performance of our loss-chasing game (Campbell-Meiklejohn et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nonetheless, some evidence that the D 2 family of receptors might play a role in learning from bad outcomes is provided by the demonstration that small single doses (0.5 mg) of the D 2 /D 3 receptor agonist, pramipexole, impair the acquisition of a response bias toward the most frequently rewarded choice in a probabilistic reward learning task, consistent with a hypothesized pre-synaptic diminution of the phasic signalling of positive prediction errors (Pizzagalli et al, 2008). This behavioral effect of low doses of pramipexole may also involve increased feedback-related neuronal responses to unexpected rewards, probably originating within the ACC region, and possibly reflecting the altered integration of decision outcomes over an extended reinforcement history (Santesso et al, 2009).…”
Section: The Role Of Distinct Dopamine Receptor Systems In Decision Mmentioning
confidence: 91%
“…The task, which has been previously validated in three independent samples (Bogdan and Pizzagalli, 2006;Pizzagalli et al, , 2008, is rooted within signal-detection theory and allows for the objective assessment of the subject's propensity to modulate behavior as a function of prior reinforcements. Briefly, in signaldetection paradigms, subjects are asked to select whether stimulus A or stimulus B was presented by making an appropriate response A or response B (McCarthy, 1991).…”
Section: Task and Proceduresmentioning
confidence: 99%